2017
DOI: 10.51804/jsh.v1i2.108.83-91
|View full text |Cite
|
Sign up to set email alerts
|

TOKSISITAS LIMBAH CAIR INDUSTRI BATIK TERHADAP MORFOLOGI SISIK IKAN NILA GIFT (Oreochomis nilotocus)

Abstract: The development of batik industry has increased along with the increasing of society requirement of textile material. Colored liquid in the batik industry has the potential to pollute the environment, so it is necessary research that aims to determine the toxicity of batik industrial waste to morphology of Nila Gift fish (Oreochromis niloticus). The test results of COD content contained in the batik industrial liquid waste is 4951,75 mg/L , analysis of TSS content of batik wastewater showed 448 mg/L, while chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
5
0
6
Order By: Relevance
“…This is different from the characteristic test of the batik industry wastewater in Yogyakarta, where BOD, COD and TSS values were obtained that exceed the quality standard (Joko dkk., 2016;Rahmadyanti & Audina, 2020). Even though this waste has gone through biological and physicochemical treatment processes (Indrayani & Triwiswara, 2018), another study that tested the quality of batik wastewater in Sidoarjo (Tangahu dkk., 2019) also produced COD and TSS values above the maximum limit for textile industrial wastewater (Andriani & Hartini, 2017). The high levels of COD in this study indicate that there were high concentrations of organic and inorganic materials that can harm the aquatic environment (Devi dkk., 2017).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…This is different from the characteristic test of the batik industry wastewater in Yogyakarta, where BOD, COD and TSS values were obtained that exceed the quality standard (Joko dkk., 2016;Rahmadyanti & Audina, 2020). Even though this waste has gone through biological and physicochemical treatment processes (Indrayani & Triwiswara, 2018), another study that tested the quality of batik wastewater in Sidoarjo (Tangahu dkk., 2019) also produced COD and TSS values above the maximum limit for textile industrial wastewater (Andriani & Hartini, 2017). The high levels of COD in this study indicate that there were high concentrations of organic and inorganic materials that can harm the aquatic environment (Devi dkk., 2017).…”
Section: Resultsmentioning
confidence: 64%
“…This means that it can give a lethal effect to 50% of the individuals tested at this concentration. Another study that tested the toxicity of batik industrial wastewater on tilapia stated that at a concentration of 1%, it caused 9.6% of fish mortality with an LC50 value of 96 hours at an interval of 0.625-0.75% (Andriani & Hartini, 2017). Susilo dkk., (2021) Liquid waste toxicity tests can be classified into several levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to goldfish scales can only be seen from the color of goldfish scales. Following Andriani and Hartini's research, the gift of tilapia seeds showed foreign substances attached to the scales exposed to batik waste 14 . Before the occurrence of lethality or death, goldfish experience changes in behavior.…”
Section: Observation Of Sublethal Effects Of Carp (C Carpio L)mentioning
confidence: 89%
“…Limbah ini harus diolah dahulu sebelum dibuang ke lingkungan. Jika langsung dibuang ke lingkungan akan menurunkan kualitas lingkungan dan merusak habitat yang hidup sekitar aliran sungai (Andriani & Hartini, 2017).…”
Section: Pendahuluanunclassified